A multi-variable, Veteran-centered study of PONV risk factors in separate regional vs. general anesthesia contexts - Schumacher, Christopher A.; Choragudi, Ridhi V.; Mikolic, Joseph M.; Boudreaux-Kelly, Monique Y.; Williams, Brian A. (Frontiers in Anesthesiology, 2025)
BackgroundCurrently, perioperative stakeholders are guided to provide general anesthesia (GA) patients with either two or four antiemetic prophylaxis (AEPPx) medications based on the 1990s legacy risk factors (RFs). There are no Veteran-centric regional anesthesia (RA) or GA postoperative nausea and vomiting (PONV) RF studies, and only a few studies have explored these factors based on race/ethnicity. Thus, the currently accepted AEPPx in Veterans may be escalating symptoms, costs, and lengths of stay.MethodsWe first conducted institutional review board (IRB)-approved secondary analyses from a prospective Veteran-specific randomized trial to assess for RA-specific PONV RFs. Subsequently, we conducted IRB-approved retrospective analyses of observational quality improvement data from Veterans receiving GA with or without intrathecal morphine (ITM) preoperatively (with ITM cases accompanied by a five-drug AEPPx). The goal was to assess both Veteran-specific and anesthesia (RA and GA)-specific PONV RFs. For RA-specific PONV RF analyses in 115 Veterans, we queried electronic medical records (EMR) along with database-archived study data from case report forms. For GA-specific PONV RF analyses in 468 Veterans, we analyzed EMR data to compare PONV-free patients with PONV-positive patients, both for postoperative days 0–1 (POD#0–1 after surgery) and POD#2.ResultsPostoperative opioids were associated with increased PONV in both analyses. For RA, African-American Veterans were found to have more PONV despite lower overall opioid consumption than that in the race-referent group, while diabetic Veterans overall showed less PONV. For GA-specific analyses (informed by the risks and signals identified in RA analyses), African-American Veterans again had more PONV. Consensus-guided RFs added to the models were often non-predictive, particularly (i) smoking status and past PONV (RA-specific) and (ii) gender and past PONV (GA-specific). This may suggest underpowering in both limited sample sizes or, instead, indicate race as a profoundly overriding RF. RFs associated with POD#2 PONV after GA (after no PONV on POD#0–1) notably differed from factors driving POD#0–1 PONV.ConclusionConsensus-guided AEPPx may require reevaluation, particularly in Veterans undergoing RA or GA, if not population-wide. All Veterans could benefit from our 2023-described off-patent five-drug AEPPx before any anesthetic drug is administered, as described herein and elsewhere. Emerging RFs may have pharmacoequity and race-based implications.